Interaction Model for Child to Cope Stress Using Virtual Reality and Watching Video during Venipuncture in the Emergency Department: A Literature Review - Permaida, Permaida; Freyana Tedja, Jane (Media Publikasi Cendekia Indonesia, 2025)
Venipuncture is the most painful and traumatic procedure often performed by nurses on pediatric patients. Innovation using technology-based interaction models is urgently needed in the emergency department. This study aims to determine the effectiveness of interaction models in reducing stress associated with venipuncture by utilizing virtual reality and video watching in the emergency department. This study employs a literature review, drawing on fourteen reputable articles from the ResearchGate, ScienceDirect, and SpringerLink databases. The results of the study based on the interaction model include (1) nurses must have a role in understanding children's stress, experience in managing children's stress, speed of completion of venipuncture procedures, and critical thinking in assessing the level of difficulty of venous access; (2) child attachment the with the importance of parental presence to suppress children's temperament; and (3) environmental aspects that support innovation in the use of virtual reality and watching videos as imaginative distraction techniques. The interaction model suggests that the roles of nurses, parental involvement, and environmental aspects can help manage the stress of children in pain in the emergency department.